China's State Energy Investment during 1991–2007: Investment Analysis and Policy Issues. Issue 10 (2nd October 2016) - Bo, Hong; Zhang, Baoshan; Oughton, Christine; Yuan, Xiaoling; Ma, Jun
Abstract : Bo H., Zhang B., Oughton C., Yuan X. and Ma J. China's state energy investment during 1991–2007: investment analysis and policy issues, Regional Studies . This article examines China's state energy investment during 1991–2007 using provincial-level panel data. The analysis shows that China's state energy investment is (1) driven by demand for energy, (2) mostly unrelated to energy efficiency, (3) undertaken with the consideration of reducing negative externalities associated with energy production, (4) used by central government to subsidize some local governments, and (5) directed to heavy industries. Policy impacts (4) and (5) are more profound in provinces in which the state's ownership of the provincial industry is high. In addition, results (4) and (5) are stronger at the earlier stage of China's domestic reform and before China's entry into the World Trade Organization (WTO), which suggests that these policy impacts weaken along with the progress of China's market transition. In sum, China's state energy investment responds to demand signals, but state ownership enables the government to implement its policy objectives, possibly at the cost of economic efficiency.